Ambassadors of the game: do famous athletes have special obligations to act virtuously?. Issue 2 (3rd May 2020) - Yorke, Christopher C.; Archer, Alfred
ABSTRACT: Do famous athletes have special obligations to act virtuously? A number of philosophers have investigated this question by examining whether famous athletes are subject to special role model obligations. In this paper, we will take a different approach and give a positive response to this question by arguing for the position that sport and gaming celebrities are 'ambassadors of the game' : moral agents whose vocations as rule-followers have unique implications for their non-lusory lives. According to this idea, the actions of a game's players and other stakeholders – especially the actions of its stars – directly affect the value of the game itself, a fact which generates additional moral reasons to behave in a virtuous manner. We will begin by explaining the three main positions one may take with respect to the question: moral exceptionalism, moral generalism, and moral exemplarism. We will argue that no convincing case for moral exemplarism has thus far been made, which gives us reason to look for new ways to defend this position. We then provide our own 'ambassadors of the game' account and argue that it gives us good reason to think that sport and game celebrities are subject to special obligations to act virtuously.